2016
DOI: 10.1249/mss.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Exercise Does Not Preferentially Mobilize Skin-Homing T Cells and NK Cells

Abstract: A small subset of CLA+ lymphocytes are mobilized into blood during acute intensive exercise, but CLA+ cells are not major contributors to exercise lymphocytosis, thus providing preliminary evidence that the skin is not a major origin, or homing destination, of exercise-sensitive lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
1
23
4
Order By: Relevance
“…Principles of the acute stress/exercise immune-enhancement hypothesis continue to be investigated. For example, it has recently been shown that acute exercise does not preferentially mobilize CD8 + T cells and natural killer cells with the capacity for skin-homing ( 118 ). However, skin-homing in this context is a role that may be fulfilled by exercise-responsive mucosal-associated invariant T cells ( 119 ); but further work is needed in this area.…”
Section: Part A: Is It Time To Close the Shutters On The “Open-windowmentioning
confidence: 99%
“…Principles of the acute stress/exercise immune-enhancement hypothesis continue to be investigated. For example, it has recently been shown that acute exercise does not preferentially mobilize CD8 + T cells and natural killer cells with the capacity for skin-homing ( 118 ). However, skin-homing in this context is a role that may be fulfilled by exercise-responsive mucosal-associated invariant T cells ( 119 ); but further work is needed in this area.…”
Section: Part A: Is It Time To Close the Shutters On The “Open-windowmentioning
confidence: 99%
“…[61][62][63] In peripheral blood, this marker has been reported to be expressed on 17% of CD4 cells and 11% of CD8 cells, 64 primarily on central and effector memory cells. 65 To our knowledge, this marker has not been examined systematically in peripheral blood of contact-allergic patients, or previously correlated with the severity of allergy. It may be that this increase in CLA expression reflects activation of T cells as a result of the patch test applied 4 days prior to the blood draw, or could represent a bystander effect, with cytokines produced by allergen-specific T cells non-specifically activating other T lymphocytes.…”
Section: The Final Features Of T Cells Isolated From Sensitized Indivmentioning
confidence: 99%
“…In study one, peripheral blood mononuclear cells (PBMCs) were collected from nine participants (age: 22.1 ± 3.4 years; height: 180.5 ± 6.1 cm; weight: 78.1 ± 11.0 kg; body mass index: 24.0 ± 3.1 kg·m 2 ; _ VO 2 MAX : 43.8 ± 4.1 ml·kg·min − 1 ) as previously described [44][45][46]. All participants were non-smokers, and refrained from taking vitamin supplements and anti-inflammatory medication for fourteen days, and did not exercise and consume alcohol of caffeine for two days prior to testing.…”
Section: Participantsmentioning
confidence: 99%
“…Values presented are the average workload over the entire exercise protocol and were obtained directly from the electromagnetically braked cycle ergometer (Lode Excalibur Sport, Groningen, Netherlands). Ratings of perceived exertion (RPE) were recorded using the Borg Scale every minute and RPE results are presented as the maximal RPE during the trial [44][45][46]. In study two, participants completed a 30 min exercise trial at a workload corresponding to +5% of the individual blood lactate threshold.…”
Section: Experimental Trialsmentioning
confidence: 99%